2023
DOI: 10.3390/biomedicines11071912
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Prostate-Specific Antigen and Its Density and Prostate Health Index and Its Density for Detection of Prostate Cancer

Abstract: As the incidence of prostate cancer (PCa) has increased, screening based on prostate-specific antigen (PSA) has become controversial due to the low specificity of PSA. Therefore, we investigated the diagnostic performance of prostate health index (PHI) density (PHID) for the detection of PCa and clinically significant PCa (csPCa) compared to PSA, PSA density (PSAD), and PHI as a triaging test. We retrospectively reviewed 306 men who underwent prostate biopsy for PSA levels of 2.5 to 10 ng/mL between January 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 34 publications
(39 reference statements)
0
3
0
Order By: Relevance
“…In a study by Chiu et al, at 90% sensitivity, 43.7% of unnecessary biopsies could be avoided when the PHID was >0.67 23 . Boo et al 19 showed that with a cutoff of PHID ≥ 0.91, PHID had a 56.2% specificity, and 49.3% of unnecessary biopsies could be avoided at the cost of 8.3% of csPCa. In this study, when applying the optimal biomarkers cutoffs, the PPV of PHI, PHID, p2PSA/fPSA, p2PSA/fPSAD was 91%, 90%, 92%, and 90% for csPCa, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a study by Chiu et al, at 90% sensitivity, 43.7% of unnecessary biopsies could be avoided when the PHID was >0.67 23 . Boo et al 19 showed that with a cutoff of PHID ≥ 0.91, PHID had a 56.2% specificity, and 49.3% of unnecessary biopsies could be avoided at the cost of 8.3% of csPCa. In this study, when applying the optimal biomarkers cutoffs, the PPV of PHI, PHID, p2PSA/fPSA, p2PSA/fPSAD was 91%, 90%, 92%, and 90% for csPCa, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…For the first time in 2014, by analogy with PSA density, PHID was introduced 17 . Tosoian et al 18 evaluated the ability of PHID in 118 men underwent first biopsy showing that PHID had the highest ability to identify csPCa (AUC 0.84), allowing to avoid 38% of unnecessary biopsies and missing only 2% of csPCa 19 …”
Section: Discussionmentioning
confidence: 99%
“…Similar to PSAD, the diagnostic performance of PHID is limited by the PV, which is indicated for patients with a PV ≤ 50 cm 3 ( 34 ). In 306 patients with a median PV of 37.9 cm 3 and PSA 4–10 ng/ml, PHID diagnosed HGPCa with an AUC of up to 0.826, which is superior to PSA, PSAD, and PHI ( 35 ). In the group of patients with a PV > 50 cm 3 , PHID demonstrated a diagnostic power similar to PSA (AUC: 0.686 vs. 0.700, respectively) ( 34 ).…”
Section: Biomarkers For the Diagnosis Of Hgpcamentioning
confidence: 95%